Impact of an Individual Mandate and Other Health Reforms on Dependent Coverage for Adolescents and Young Adults. (30th May 2017) - Wisk, Lauren E.; Finkelstein, Jonathan A.; Toomey, Sara L.; Sawicki, Gregory S.; Schuster, Mark A.; Galbraith, Alison A.
Abstract : Objective: To determine the effect of state‐level dependent coverage expansion (DCE) with and without other state health reforms on exit from dependent coverage for adolescents and young adults (AYA). Data Sources: Administrative longitudinal data for 131, 542 privately insured AYA in Massachusetts (DCE with other reforms) versus Maine and New Hampshire (DCE without other reforms) across three periods: prereform (1/00–12/06), poststate reform (1/07–9/10), and postfederal reform (10/10–12/12). Study Design: A difference‐in‐differences estimator was used to determine the rate of exit from dependent coverage, age at exit from dependent coverage, and re‐uptake of dependent coverage among AYA in states with comprehensive reforms versus DCE only. Principal Findings: Implementation of DCE with other reforms was significantly associated with a 23 percent reduction in exit from dependent coverage among AYA compared to the reduction observed for DCE alone. Additionally, comprehensive reforms were associated with over two additional years of dependent coverage for the average AYA and a 33 percent increase in the odds of regaining dependent coverage after a prior loss. Conclusions: Findings suggest that an individual mandate and other reforms may enhance the effect of DCE in preventing loss of coverage among AYA.